Microstructures, mechanical properties and cytotoxicity of low cost beta Ti–Mn alloys for biomedical applications. (15th October 2015) - Santos, Pedro Fernandes; Niinomi, Mitsuo; Cho, Ken; Nakai, Masaaki; Liu, Huihong; Ohtsu, Naofumi; Hirano, Mitsuhiro; Ikeda, Masahiko; Narushima, Takayuki
Graphical abstract: The low cost β-type Ti–9Mn exhibits superior tensile properties than those of Ti–6Al–4V ELI. The cell viability ratio of Ti–9Mn is comparable with that of CP-Ti. These results are promising for biomedical applications. Abstract: The microstructures, mechanical properties and biocompatibility of low cost β-type Ti-(6-18)Mn alloys were investigated after solution treatment. Ti–9Mn exhibits the best combination of tensile strength and elongation among the fabricated alloys, and its performance is comparable to or superior to those of Ti–6Al–4V ELI (Ti-64 ELI) in terms of every parameter evaluated. A hardness of 338 HV, a Young's modulus of 94 GPa, a 0.2% proof stress of 1023 MPa, an ultimate tensile strength of 1048 MPa and elongation of 19% were obtained for Ti–9Mn. Furthermore, the cell viability and metallic ion release ratios are comparable to those of commercially pure titanium, making this alloy promising for biomedical applications. The Young's modulus is also lower than that of Ti-64 ELI (110 GPa), which can possibly reduce the stress shielding effect in implanted patients. Statement of significance: This study evaluates mechanical and biological performance of low cost solution treated β-type Ti-(6, 9, 13 and 18 mass%)Mn alloys. It includes alloys containing a Mn content range higher than most previously published works (which is around or lower than 8 mass%). Furthermore, the effects of the ω phase and the β phase stability of the alloys over some mechanical properties and microstructures are discussed. Ion release behavior under simulated body fluids and cell viability are also evaluated. For the case of the Ti–9Mn, a mechanical and biological performance that is comparable to or superior than that of the widely used Ti–6Al–4V ELI and commercially pure Ti was observed.